Credit Risk Management and Financial Performance of Microfinance Institutions in Uganda: A Case Study of Brac Microfinance Namukasa Branch Kayunga Road and Seeta Branch Seeta Trading Centre Mukono District - Dinavence Asiimire (Uganda Christian University, 2024)
The study concerning the findings on credit risk management and financial performance of Brac Microfinance. The study objectives were to investigate the credit risk management practices used by Brac microfinance, to find out the relationship between credit risk management and financial performance and lastly to identify the challenges facing the microfinance institution with their possible solutions. The study was conducted from 49 respondents who were the employees of Brac Microfinance. The data was collected using closed ended questionnaires were data, the research was entirely a descriptive research design based on quantitative research. The study findings revelaed that credit risk management had a significant contribution to financial performance. The study concluded that credit risk management practices used were client appraisal, collateral requirements and loan restructuring and recovery on the first objective, on the second objective it was concluded that the relationship was evident but complex strong correlations were observed between credit risk identification and monitoring with key financial performance and on the third objective it was concluded that the microfinance was facing challenges such as credit risk and client outreach. The study recommends that Brac microfinance should consider integrating more advanced credit scoring models and continuously updating them based on emerging data to improve accuracy and effectiveness, prioritize enhancing its monitoring systems and it should also focus on improving financial planning and resource management.